Experimental and Computational Analysis on the Acoustic Performance of Side Outlet Muffler with Semi-Circular Baffles - VISHWAKARMA, Sandeep Kumar; PAWAR, Suryappa Jayappa (Archives of Acoustics, 2025)
In this study, the impacts of the inclusion of two semi-circular baffles and their orientations on the acoustic performance of the side outlet muffler have been investigated. The side outlet muffler has a circular simple expansion chamber with an axial inlet and a side outlet and two semi-circular baffles that have been placed inside the expansion chamber at different orientations. The axis of the outlet is at the right angle to the axis of the inlet. The acoustical investigation of the side outlet muffler with two semi-circular baffles is done using the plane wave analysis, the finite element method (FEM), and the two-load technique. Based on the orientations of the two semi-circular baffles, three different models of side outlet muffler with semi-circular baffles have been investigated. The plane wave analysis, FEM, and two-load method are applied to all models and it is found that analytical, computational, and experimental transmission loss (TL) are in good agreement. The analytical modelling successfully predicts the presence of semi-circular baffles in the form of peaks and troughs in the TL of side outlet muffler with semi-circular baffles before the cut-off frequency and thus proves its effectiveness. Among all the models, model_2 gives 42 % higher TL than model_1 and model_3 shows 16.20 % higher TL than model_2. Hence, model_3 proves to be the best design for the side outlet muffler with semi-circular baffles in the attenuation of noise. The model_3 is effective for 1030 Hz–1480 Hz, 1500 Hz–1570 Hz, and 1640 Hz–2400 Hz frequency sound waves. The TL curve, sound pressure contours for model_3, and the band power variation in the 1/3 octave band for all the models have also been presented.